2020
DOI: 10.7554/elife.56840
|View full text |Cite
|
Sign up to set email alerts
|

True S-cones are concentrated in the ventral mouse retina and wired for color detection in the upper visual field

Abstract: Color, an important visual cue for survival, is encoded by comparing signals from photoreceptors with different spectral sensitivities. The mouse retina expresses a short wavelength-sensitive and a middle/long wavelength-sensitive opsin (S- and M-opsin), forming opposing, overlapping gradients along the dorsal-ventral axis. Here, we analyzed the distribution of all cone types across the entire retina for two commonly used mouse strains. We found, unexpectedly, that ‘true S-cones’ (S-opsin only) are highly conc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
108
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 83 publications
12
108
1
Order By: Relevance
“…Seven days after LIP, mice were perfused transcardially and briefly with saline, followed by 4% paraformaldehyde in 0.1 M pH 7.2 phosphate buffer, and then retinal whole-mounts were prepared with the vitreous-side down, following a standard protocol previously developed in our laboratory [ 5 , 18 , 45 , 46 ]. Retinal wholemounts were used to immunodetect S-opsin with a primary antibody against S-opsin (goat anti-OPN1SW; 1:1000; Santa Cruz Biotechnologies), which in the albino mouse retina recognize ≈96% of all cone outer segments [ 18 , 20 , 35 ]. This was followed with a secondary antibody Alexa Fluor-488 donkey anti-goat (1:500; IgG (H + L), Molecular Probes, Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven days after LIP, mice were perfused transcardially and briefly with saline, followed by 4% paraformaldehyde in 0.1 M pH 7.2 phosphate buffer, and then retinal whole-mounts were prepared with the vitreous-side down, following a standard protocol previously developed in our laboratory [ 5 , 18 , 45 , 46 ]. Retinal wholemounts were used to immunodetect S-opsin with a primary antibody against S-opsin (goat anti-OPN1SW; 1:1000; Santa Cruz Biotechnologies), which in the albino mouse retina recognize ≈96% of all cone outer segments [ 18 , 20 , 35 ]. This was followed with a secondary antibody Alexa Fluor-488 donkey anti-goat (1:500; IgG (H + L), Molecular Probes, Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Blue light, the most damaging component of sunlight, causes oxidative stress that induces the loss of retinal pigment epithelium cells and photoreceptors [ 13 , 14 , 15 , 16 , 17 , 18 ]. We have recently characterized a new focal blue light emitting diode (LED) induced phototoxicity (LIP) model in albino mice that results in focal phototoxic cone degeneration in an area of the retina that coincides with the highest density of rodent photoreceptors [ 16 , 18 , 19 , 20 ]. This model allows automatic quantification of S-cone outer segments (OS) that is appropriate for determining the efficacy of different neuroprotective drugs [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, mice lacking cone function to assess rod saturation will not be subject to the substantial cone-rod crosstalk in the mouse (Demb and Singer, 2012;Grimes et al, 2018). Furthermore, more recent studies have shown that photoreceptor distributions and retinal circuits are more demarcated along the dorsoventral axis than originally thought (Joesch and Meister, 2016;Nadal-Nicolás et al;Szatko et al, 2020). As a result, rod-cone interactions may also affect rod saturation in mice with normal retinas, in a retinotopic-dependent fashion.…”
Section: The Required Light Levels To Reach Cone-mediated Responses Cmentioning
confidence: 99%
“…Next to a medium (M) wavelength-sensitive opsin peaking at 510 nm (green), mice have a short (S) wavelength-sensitive opsin peaking at 360 nm in the UV (Jacobs et al, 2004;Röhlich et al, 1994) . Due to co-expression of the S-opsin in ventral M-cones (Baden et al, 2013;Szél et al, 1992) and a peak in S-cone density in the ventral periphery (Nadal-Nicolás et al, 2020) , the mouse retina is subdivided into a more green-sensitive dorsal and a strongly UV-sensitive ventral half. Notably, ventral cones are tuned to signal dark contrasts (Baden et al, 2013) and, hence, may support the detection of dark shapes against the sky.…”
Section: Introductionmentioning
confidence: 99%